0
161views
Determine the frequency response and impulse response, $$y(n)-\frac{1}{6} y(n-1)-\frac{1}{6} y(n-2)=x(n)$$
0
2views

Solution:

$y(n)-\frac{1}{6} y(n-1)-\frac{1}{6} y(n-2)=x(n)\$

Applying DTFT,

$Y\left(e^{j \omega}\right)-\frac{1}{6} e^{-j \omega} Y\left(e^{j \omega}\right)-\frac{1}{6} e^{-2 j \omega} Y\left(e^{j \omega}\right)=X\left(e^{j \omega}\right)\$

Frequency response,

$H\left(e^{j \omega}\right)=\frac{Y\left(e^{j \omega}\right)}{X\left(e^{j \omega}\right)}=\frac{1}{1-\frac{1}{6} e^{-j \omega}-\frac{1}{6} e^{-2 j \omega}}\\$

$=\frac{e^{2 j \omega}}{e^{2 j \omega}-\frac{1}{6} e^{j \omega}-\frac{1}{6}}\\$

$\begin{gathered}\\ \frac{H\left(e^{j \omega}\right)}{e^{j \omega}}=\frac{e^{j \omega}}{e^{2 j \omega}-\frac{1}{6} e^{j \omega}-\frac{1}{6}}=\frac{A}{e^{j \omega}-\frac{1}{2}}+\frac{B}{e^{j \omega}+\frac{1}{3}} \\\\ e^{j \omega}=A\left(e^{j \omega}+\frac{1}{3}\right)+B\left(e^{j \omega}-\frac{1}{2}\right)\\ \end{gathered}$

\begin{aligned} & \text { At } e^{j \omega}=\frac{1}{2} \\\\ & \frac{1}{2}=A\left(\frac{1}{2}+\frac{1}{3}\right)\\ \end{aligned}\\

$\therefore A=\frac{3}{5}\\$

$H\left(e^{j \omega}\right)=\frac{\frac{3}{5} e^{j \omega}}{e^{j \omega}-\frac{1}{2}}+\frac{\frac{2}{5} e^{j \omega}}{e^{j \omega}+\frac{1}{3}}\\$

Applying inverse DTFT,

$h(n)=\frac{3}{5}\left(\frac{1}{2}\right)^n u(n)+\frac{2}{5}\left(-\frac{1}{3}\right)^n u(n)\\$